Verba Beri-Terima dalam Bahasa Jepang - Akhmad Saifudin (Japanese Research on Linguistics, Literature, and Culture, 2021)
One of the characteristics of Japanese that is different from other languages is the use of the verbs giving and receiving. The variety of verbs of giving and receiving in Japanese is more numerous and involves factors outside the language. In this paper, we discuss how to use the verbs of giving and receiving in terms of internal factors in the Japanese language and culture. By using a qualitative paradigm, the data were analyzed using the verb give-accept. The theories used include Japanese syntactic and semantic theory, sociolinguistics, and Japanese culture. From the results of the analysis, it was found that in understanding its use, it is necessary not only to understand linguistics but also to understand Japanese socio-culture. An understanding of social concepts is needed, especially the dichotomy of social distance “Uchi-Soto” and social status “jogekankei” to determine the variety and style of verbs used. Cultural factors about empathy are also important to determine the level of empathy that a speaker gives based on his point of view.